Corporate tax incentives and capital structure: New evidence from UK firm-level tax returns - Devereux, Michael P.; Maffini, Giorgia; Xing, Jing (Journal of Banking & Finance, 2018)
We investigate how companies’ capital structure is affected by corporate income taxes using confidential company-level tax returns for a large sample of UK firms. Exploiting variation in companies’ marginal tax rates, we find a positive and substantial long-run tax effect on leverage. Leverage responds more to decreases in the marginal tax rate, and it responds to changes in the marginal rather than the average tax rate. Most importantly, we find that the marginal tax rate based on tax returns has greater explanatory power for companies’ leverage than the marginal tax rate based on financial statements. Our study suggests that errors in the measurement for tax incentives using financial statements could lead to underestimation of the tax effects on capital structure.